Estimation of heritability for growth traits of Red Chittagong cattle in a nucleus herd (Bangladesh Veterinarian, 2011)
The present study was undertaken to estimate the heritability for growth traits in a nucleus herd of Red Chittagong cattle (RCC) using data from 2005 to 2010. The traits considered were birth weight, weight at three-month intervals from birth to 24 months, and pre-weaning and post-weaning growth rate. The mean pooled weight (mean ± se) of 127 RCC calves from birth to 24 months at three month intervals were 14.7 ± 0.2, 29.3 ± 6.1, 42.6 ± 9.2, 55.0 ± 12.4, 66.2 ± 15.5, 74.5 ± 16.0, 86.1 ± 23.5, 98.8 ± 24.8 and 111.6 ± 25.2 kg, respectively. The pre- and post-weaning growth rates were 148.5 ± 45.0 and 116.6 ± 56.5 g/day, respectively. The pre-weaning growth rate was significantly (P